The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/humu.21552
|View full text |Cite
|
Sign up to set email alerts
|

A novelGJA3mutation associated with congenital nuclear pulverulent and posterior polar cataract in a chinese family

Abstract: Congenital cataract (CC) is the leading cause of visual disability in children. To date, mutations in many genes have been linked to CC. In a four-generation Chinese family with congenital nuclear pulverulent and posterior polar cataracts, we detected a heterozygous c.5G>A transition in the second exon of GJA3, resulting in the substitution of a highly conserved glycine with aspartic acid (p.G2D) at the N-terminus of the connexin46 (Cx46) protein. Wild type (wt) and mutant Cx46 plasmids were transfected into H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
(9 reference statements)
1
12
0
Order By: Relevance
“…Such cells express PDGFR and can be stimulated by PDGF. Previous reports on cells have confirmed that PDGF can promote cell proliferation and transformation to mesenchymal cells (Yao et al, 2011). Our clinical results confirmed that PDGF-α was overexpressed in the higher lesion.…”
Section: Discussionsupporting
confidence: 88%
“…Such cells express PDGFR and can be stimulated by PDGF. Previous reports on cells have confirmed that PDGF can promote cell proliferation and transformation to mesenchymal cells (Yao et al, 2011). Our clinical results confirmed that PDGF-α was overexpressed in the higher lesion.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, different Cx46 mutations have been associated with leaky HCs. For example, mutant Cx46G143R (located in the IL) leads to the appearance of Coppock cataracts ( Ren et al, 2013 ), and mutant Cx46G2D (located the NT) has been linked to formation of nuclear pulverulent and posterior polar cataracts ( Yao et al, 2011 ). Lower plasma membrane expression of these mutants was enough to promote cell death when expressed in HeLa cells ( Ren et al, 2013 ).…”
Section: Leaky Hcsmentioning
confidence: 99%
“…Cx50G46V forms normal gap junctions, but it increased hemichannel activity [20] . Cx46G2N reduces hemichannel permeability, but it still forms gap junction plaques [11] . Moreover, Cx46G143R increases hemichannel function and causes apoptosis, even when the transfected cells are cultured at low density with minimal gap junctions [40] .…”
Section: Discussionmentioning
confidence: 99%
“…The cells were washed twice with Ca 2+ -free HBSS (Gibco). Dye uptake assays were performed by incubating each group of cells in Ca 2+ -free HBSS (Gibco) and in HBSS containing 1.2 mmol/L Ca 2+ or a specific hemichannel blocker, flufenamic acid (FFA, 300 µmol/L, Sigma, Saint Louis, MO, USA) [11] . All of the solutions were supplemented with 0.1% propidium iodide (PI, Sigma) or 0.1% 4′,6-diamidino-2-phenylindole (DAPI, Sigma).…”
Section: Methodsmentioning
confidence: 99%